Inequality of Policy on Work-Area Relocation Patterns Reflected in Female Examiners through a Phenomenological Approach - Jesica Nuraini; Diana Teresa Pakasi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Implementing gender mainstreaming in realizing gender equality has not been executed optimally in BPK. This inequality could be portrayed through the implementation of mandatory rotation. This research aims to describe the inequality in the office due to the mandatory rotation. The author uses qualitative and phenomenology to depict the problems. Furthermore, the Gender at Work analytical framework proposed by Rao et al. (2016) reflects the experiences of female auditors regarding the inequality encountered in the process of mandatory rotation. The notion of Gender at Work has 4 (four) quadrants that are supposed to link to each other. Those quadrants include Consciousness and Capability, Resources, Rules and Policy, Social Norms, and Deep Structures. There are 3 (three) informants involved in this research: female auditors with 10 (ten) years of experience working. The data was collected by conducting the interview. The conclusion found is that the quadrant of consciousness and capability, as well as resources, influenced each other. In addition, consciousness and capability also influenced quadrants of rules and policies, although the latter did not. The quadrants of consciousness and capability, along with social norms and deep structure, influence each other. At the same time, the social norms and deep structure is also influenced by the quadrants of rules and policies.